Reducing inappropriate investigations for minor lower limb cellulitis - Poh Yong Tan; Leer Liang; Daryl Yin Keong Lo; Elaine Jing-Mei Pang; Elizabeth Ming Jing Tan; Adrian Chung Thien Lim; Calyn Marini Eng Lian Yap (BMJ Open Quality)
Lower limb cellulitis is a frequently encountered condition in the acute hospital setting, yet many patients with only mild lower limb cellulitis undergo unnecessary collection of blood cultures and X-ray imaging. This leads to increased healthcare costs and prolongation of the length of hospitalisation.A retrospective review of electronic medical records was performed to determine the frequency of blood cultures and lower limb X-rays performed for patients with lower limb cellulitis presenting to the Department of Emergency Medicine and admitted to the Department of Internal Medicine, in a national tertiary hospital.Quality improvement methods were implemented to increase accessibility to and awareness of lower limb cellulitis management guidance among clinical staff, to empower appropriate and rationalised decision-making in the management of patients with lower limb cellulitis. The percentage of patient encounters with blood cultures performed subsequently improved from a baseline median of 73.3% to a post-intervention median of 52.3%, with direct healthcare cost savings and additional ancillary beneficial effects for patients and healthcare staff. However, no reduction in the frequency of imaging performed was observed, for which the opportunity arises for further root-cause analyses and intervention.Encouraging small changes in individual clinicians’ routine daily clinical practice through quality improvement initiatives results in significant impacts when multiplied across healthcare staff and departments. Initiatives implemented need to be accessible, realistic and pragmatic to maximise real-world on the ground effects and facilitate a sustained impact.